I Am Special : Introducing children and young people to their autistic spectrum disorder - Vermeulen, Peter (London : Jessica Kingsley, 2000)
This workbook is designed for use by and with young people with autism spectrum disorder. Acting as an excellent source of information for the autistic child, and containing exercises and information, it can be used to counsel as well as to teach.
Includes bibliographical references and index.
Keywords: Autistic children; Autistic youth; Autism -- Problems, exercises, etc; Health and Fitness